Synthesis and antimicrobial activity of new phthalocyanine complexes and electrochemical and spectroelectrochemical behaviour of cobaltphthalocyanine - (:unkn) unknown (SCIENCE REVIEWS 2000 LTD, 2012)
A novel phthalocyanine bearing oxygen donor atoms on the peripheral positions has been synthesised by cyclotetramerisation of (E)-4-(4-cinnamoylphenoxy)phthalonitrile and its nickel, zinc, cobalt, copper and lead derivatives prepared. The thermal stabilities of the phthalocyanine compounds have been determined and their possible biological activities (antibacterial, anticandidal and antifungal) studied. The effects of substituent on the electrochemical and in situ spectroelectrochemical behaviour of cobaltphthalocyanine have been investigated and an in situ electrocolorimetric method was applied to investigate the colour of the electrogenerated anionic and cationic forms of the complex.
Keywords: phthalocyanine; metal complexes; antimicrobial activity; spectroelectrochemistry; chromaticity diagram; MICROWAVE-ASSISTED SYNTHESIS; GRAM-NEGATIVE BACTERIA; PHOTODYNAMIC THERAPY; DIAZADITHIA MACROCYCLES; INCLUSION COMPLEXES; CATALYTIC-ACTIVITY; METAL-FREE; METALLOPHTHALOCYANINES; SUBSTITUENTS; PORPHYRINS